DESIGN OPTIMIZATION OF THE PLOUGH WORKING SURFACE BY COMPUTERIZED MATHEMATICAL MODEL - Formato, Andrea; Ianniello, Domenico; Villecco, Francesco; Lenza, Tony Luigi Leopoldo; Guida, Domenico (Emirates Journal of Food and Agriculture, 2017)
In this paper, a procedure for the optimization of the working surface of a plough for a soil type considered and to analyze the efficiency, is performed. It fits in the set of numerical – experimental techniques used for the improvement of the energy performance related to ploughing of agricultural soil. In the first part of this paper, it describes how to generate a family of working surfaces for assigned geometrical and process parameters; latter, by mean the use of a physical-mathematical model which describes the soil - plough interaction, it is examined the draught resistance changing in function of the geometric and process parameters for a soil considered, aimed to optimize the shape. A commercially available plough, subsequently, was examined and, applying such methods, its parametric representation and the optimized surface were obtained for the examined soil.